Successful Management of Hysterocele in a Pregnant Goat - Varshini, Avula Vijaya; Lakde, Chetan Kishorrao; Raghuwanshi, Dilip Singh; Gawande, Ajay Pandurangrao; Patil , Manoj Subhash (The Indian Journal of Animal Reproduction, 2025)
A female goat with a full term pregnancy aged 1 1⁄2 year was reported to Teaching Veterinary Clinical Complex, Nagpur with the complaint of swelling in the ventral abdomen for one week. Fetal parts were able to palpate at the swollen part. On genital examination, it was observed that the fetus is not in the pelvic cavity. By ultrasonographic examination, a fully developed fetal skeleton with no cardiac activity was noticed. The swollen abdomen indicated that the fetus might come away from the uterus. It was diagnosed as a rare case of “Hysterocele”. Immediately, Cesarean section was done asepti cally and the dead fetus was removed manually. Hernial part was corrected by Herniorrhaphy. Fluid therapy, antibiotics, antihistamine injections were given for one week. Animal was recovered by exhibiting normal behaviour within 15 days.
Keywords: Goat; Hysterocele; Cesarean Section; Herniorraphy